Investigation of follicular helper T cells, as a novel player, in preeclampsia. Issue 3 (27th September 2018) - Heydarlou, Hanieh; Eghabl‐Fard, Shadi; Ahmadi, Majid; Aghebati‐Maleki, Leili; Dolati, Sanam; Movassaghpour, Ali Akbar; Jadidi‐Niaragh, Farhad; Danaei, Shahla; Mahmoudilafout, Farzaneh; Talebi, Mehdi; Rahimifar, Shahrzad; Yousefi, Mehdi
Abstract: Preeclampsia (PE) is characterized by hypertension and proteinuria. It occurs in an around 3% to 5% of all pregnancies worldwide. The fetus is kind of semiallograft to the maternal host; immune system components encounter fetal antigens and develop adverse immune responses. Recently, it has been observed that the immune system plays an important role in PE. In the current study, we have tried to investigate the role of follicular helper T (Tfh) cells in the pathogenesis of PE. Blood samples of 49 PE women and 50 healthy controls were collected. Peripheral blood mononuclear cells were isolated, cells were cultured, and then RNA was extracted. Autoantibody and secretory cytokine levels were analyzed by ELISA. Tfh frequency and transcription levels of the related molecules and cytokine were assessed by flow cytometry and real‐time PCR, respectively. The frequency of circulating Tfh cell in PE women was significantly higher compared with the healthy pregnant woman (Tfh cells with CD4 + ICOS +, P = 0.0064 and Tfh cells with CD4 + CXCR5 +, P = 0.029). Moreover, mRNA expression levels of CXCR5, BCL6, IL‐21, and IL‐6 ( P = 0.0006, P = 0.008, P = 0.0063, and P = 0.027, respectively) were upregulated in PE patients. Furthermore, IL‐6 ( P = 0.0014) and IL‐21 ( P = 0.0059) levels in both group were assayed and the results showed increased in patient group. We also measured autoantibody levels including antiphospholipid antibodies ( P = 0.0001), anticardiolipin antibodies ( P = 0.0004), anti‐TPO ( P = 0.0008), anti‐TG ( P = 0.001) in circulation of PE group, which were higher than the control group. This study provided insights into the involvement of Tfh cells in etiology and pathogenesis of PE, probably by developing autoantibodies.